Crustal Structure at a Young Continental Rift: A Receiver Function Study From the Tanganyika Rift. Issue 12 (5th December 2017) - Hodgson, Isabel; Illsley‐Kemp, Finnigan; Gallacher, Ryan J.; Keir, Derek; Ebinger, Cynthia J.; Mtelela, Khalfan
Abstract: The southern Tanganyika Rift, within the Western rift, Africa, has earthquakes to depths of 37 km, yet few constraints exist on crustal thickness, or of early stage rifting processes in apparently amagmatic rift sectors. The aim of the TANGA14 experiment was to constrain bulk crustal properties to test whether magmatic processes modify the lithosphere in areas of deep seismicity, and the degree of lithospheric thinning. We use 11 broadband seismometers to implement receiver function analysis using H ‐ κ stacking, a method sensitive to crustal thickness and V P / V S ratio, to determine bulk crustal properties. Analyses include extensive error analysis through bootstrap, variance, and phase‐weighted stacking. Results show the Archean Tanzanian Craton and Bangweulu Block are characterized by V P / V S ratios of 1.75–1.77, implying a felsic bulk composition. Crust beneath the fault‐bounded basins has high V P / V S (>1.9). Anorthosite bodies and surface sediments within the region may contribute to localized high V P / V S . However, elevated V P / V S values within fault‐bounded extensional basins where elevated heat flow, hydrothermal vent sites, and deep earthquakes are observed suggest that magma may be intruding the lower crust beneath the southern Tanganyika Rift. Crustal thicknesses on/near the relatively unextended Tanzanian craton and Bangweulu Block are 41.6–42.0 km. This contrasts with the Tanganyika Rift where crustal thicknesses are 31.6 km to 39 km from north to south. Our results provide evidence for ~20% crustal thinning localized to fault‐bounded basins. Taken together, they suggest a previously unrecognized role of magma intrusion in early stage continental rifting in the Western rift, Africa. Key Points: We present the first detailed study of crustal structure at Lake Tanganyika using receiver functions inversion and forward modeling Crustal thinning along the eastern Tanganyika rift basin is ~20% but may increase beneath the central basin Elevated V P / V S ratios, evidence for gradational Moho, and deep seismicity suggest previously unrecognized role of magma intrusion